The influence of some cultural treatments on the development and yield of potatoes on the Cape Flats - Rocher, P. M.(Pierre Mackenzie) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1958.